Assessment of health and economic effects by PM2.5 pollution in Beijing: a combined exposure–response and computable general equilibrium analysis. Issue 24 (16th December 2016) - Wang, Guizhi; Gu, SaiJu; Chen, Jibo; Wu, Xianhua; Yu, Jun
ABSTRACT: Assessment of the health and economic impacts of PM2.5 pollution is of great importance for urban air pollution prevention and control. In this study, we evaluate the damage of PM2.5 pollution using Beijing as an example. First, we use exposure–response functions to estimate the adverse health effects due to PM2.5 pollution. Then, the corresponding labour loss and excess medical expenditure are computed as two conducting variables. Finally, different from the conventional valuation methods, this paper introduces the two conducting variables into the computable general equilibrium (CGE) model to assess the impacts on sectors and the whole economic system caused by PM2.5 pollution. The results show that, substantial health effects of the residents in Beijing from PM2.5 pollution occurred in 2013, including 20, 043 premature deaths and about one million other related medical cases. Correspondingly, using the 2010 social accounting data, Beijing gross domestic product loss due to the health impact of PM2.5 pollution is estimated as 1286.97 (95% CI: 488.58–1936.33) million RMB. This demonstrates that PM2.5 pollution not only has adverse health effects, but also brings huge economic loss.